High-Molecular-Weight Glutenin 1Bx17 and 1By18 Subunits Encoded by Glu-B1i Enhance Rheological Properties and Breadmaking Quality of Wheat Dough. (4th June 2019) - Guo, Haoyu; Wu, Jisu; Lu, Yuxia; Yan, Yueming
Abstract : The elasticity of wheat dough is mainly determined by high-molecular-weight glutenin subunits (HMW-GSs) encoded by Glu-1 loci. In this study, we performed the first comprehensive study on the effects of Glu-B1i -encoded 1Bx17 and 1By18 subunits on dough rheological properties and breadmaking quality by using a pair of Glu-B1 near-isogenic lines (NILs) ZM-NIL1 and ZM-NIL2. Comparative analysis of basic quality parameters, rapid visco analyzer (RVA) and farinograph parameters, and C-cell and loaf parameters showed that ZM-NIL2 containing Glu-B1i -encoded 1Bx17 and 1By18 subunits had better dough rheological properties and breadmaking quality than ZM-NIL1 carrying Glu-B1c -encoded 1Bx7 and 1By9 subunits, including significantly increased protein and gluten content, development time and stability, and loaf volume and score. Particularly, 1Bx17 and 1By18 subunits could significantly enhance bread texture, including significant increase in slice brightness, slice area, circumference, cell contrast, cell extension, and cell quantity. These results demonstrate that 1Bx17 and 1By18 subunits have a significant contribution to dough rheological properties and breadmaking quality.